Pengaruh Dukungan Sosial terhadap Kesejahteraan Psikologis Karyawan di Tempat Kerja - Mayreyna Nurwardani; Zayyina Taqiyya Azka; Shanazfi Rizki Nur'aini; Baiq Ayu Pratiwi Safitri (CV. Era Digital Nusantara, 2026)
Employee psychological well-being is an important aspect in industrial relations which currently faces various challenges due to high job demands, technological changes, and post pandemic pressures. The phenomenon of declining psychological well-being among employees often appears in the form of work stress, burnout, anxiety, and decreased motivation. This study uses a qualitative method in the form of literature review based on various theoretical sources, journal articles, and previous relevant studies. The literature analysis results show that social support has a positive and significant influence on employees’ psychological well-being. Social support act as a protective factor that can reduce the negative impact of job demands. There are three main forms of social support that have strongest influences; supervisor support, co-worker support, and perceived organizational support. Social support not only reduces the risk of burnout and work stress but also increases job satisfaction, organizational commitment, and employee productivity.